Validation of an innovative analytical method for simultaneous quantification of curcumin and fluconazole using high-performance liquid chromatography from nanostructured lipid carriers - Araujo, Victor Hugo Sousa [UNESP]; Fernandes, Lígia de Souza [UNESP]; dos Reis, Leidiana Rocha [UNESP]; Carvalho, Gabriela Corrêa [UNESP]; Scarpa, Maria Virginia [UNESP]; Chorilli, Marlus [UNESP] (Wiley, 2021)
Vulvovaginal candidiasis is a public health problem with a high incidence among female patients. Currently, there is an increase in the identification of Candida spp. resistant to current therapy, making it necessary to search for new therapeutic alternatives. The synergistic potential of curcumin with fluconazole is described in the literature. However, due to its high lipophilicity, it is necessary to use drug-delivery systems to adequately explore its potential, among which is the nanostructured lipid carrier. However, to date, there is no validated method of high-performance liquid chromatography for simultaneous determination of fluconazole and curcumin in the literature. Thus, the present work developed a high-performance liquid chromatography method for simultaneous determination of fluconazole and curcumin co-encapsulated in nanostructured lipid carrier which was validated according to the International Conference on Harmonization (Technical Requirements for Registration of Pharmaceuticals for Human Use) – Q2 (R1) and the Food and Drug Administration - Guidance for Bioanalytical Method. The method was applied to determine the encapsulation efficiency and drug-loading of curcumin and fluconazole in nanostructured lipid carriers. The developed method proved to be selective, precise, accurate, and robust for the simultaneous determination of both drugs, enabling the quantification of encapsulation efficiency and drug-loading of curcumin and fluconazole in nanostructured lipid carriers.
Keywords: curcumin; fluconazole; nanostructured lipid carriers; simultaneous detection